Potential of Sodium Alginate in Sargassum sp. in Lotion Preparation to Treat Incision Wound in Mice - Amelia Cahya Angelina; Ervia Yudiati; Delianis Pringgenies (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Sargassum sp. is a known genus of brown seaweed whose dominant component is alginic acid or alginate. Various studies found that alginate having proinflammatory activity, so it may have potential to improve the wound healing process. This study aimed to obtain sodium alginate extract and to know the potency of the sodium alginate extract in incision wound treatment in mice abdomen. Lotion application was performed once a day in a span of five consecutive days. Observation on the wound was carried out to obtain data on blood coagulation, tissue reparation, and fibroblast development rate on the wound using histology. The results showed that the average yield from the Sargassum sp. extraction process was 31.3%. Quality control of the prepared lotion included organoleptic test; light brown coloration, lotion specific odor, semi- solid texture. The acidity of the lotion was measured as 6.61 with 6.731 cp of viscosity. The lotion adhesiveness test showed 0.21 seconds and the lotion was shown to be oil-in-water. Application of the lotion on incision wounds made in the abdomen of rats showed blood coagulation on the first day and onset of wound reparation process on the second day. Wound observation by the third day showed that the inflicted area had undergone a near-complete reparation. The study also showed that on the fifth day of reparation Sargassum sp. extract lotion treatment group showed fibroblast formation, as opposed to the non-extract lotion treatment group. Previous study use alginates as wound dressing material, but in this study alginate used as active ingredient in wound healing treatment. Therefore, this study concludes that sodium alginate in Sargassum sp. seaweed has a potential application in the field of medicine.